Composite material and preparation method thereof, dividing cone and preparation method thereof
By using composite materials, using the squeezing casting process of ceramic particles and high chromium cast iron to prepare a wear -resistant material cone, solve the problem of severe grinding of existing materials and short service life, and achieve more efficient Darration durability and lower energy consumption.
Patent Information
- Application Number
- CN202011645320.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-12-31
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-12-31
AI Technical Summary
The existing material separator cones wear severely during high-speed rotation, have short service life, and are cumbersome to replace, which affects user efficiency.
The composite material is used to prepare the material cone to make the ceramic particles, adhesives, and water glass sintering more porous ceramic prefabricated bodies, and fill its pores with high chromium cast iron and other materials to form wear -resistant composite materials by squeezing.
It significantly increases the service life of the material division cone, a life span of more than 3 times, and at the same time reduced the weight of the material and the power output of the motor, and reduced the bearings of the bearing.
Smart Images

Figure CN112808978B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of crushers, and in particular to a composite material and a preparation method thereof, a dividing cone and a preparation method thereof. Background Art
[0002] The rotor components of the vertical shaft crusher include a dividing cone, a throwing head and a guide plate. After the ore and other materials enter the rotor body through the drop port, under the action of high-speed rotation (angular velocity of 1000-2000r / min), the ore material is accelerated to a higher linear velocity by centrifugal force and thrown out. The material will produce a lot of friction with the dividing cone, causing the dividing cone to wear and fail too quickly, and the general life span is only 100-200h. Because the dividing cone is large in size and heavy in weight, the dividing cone of some large vertical shaft crushing equipment is >100kg. Therefore, the daily disassembly and replacement of this part is very troublesome, time-consuming and labor-intensive, at least half a day, which seriously affects the user's efficiency.
[0003] The existing dividing cones are mainly made in the following three ways: 1. Gravity casting with high-chromium cast iron; 2. Inlaying carbide columns in high-chromium cast iron alloy; 3. Using welding wire to weld carbide on the surface of the dividing cone parts. However, the dividing cones made by the above methods have the following disadvantages: 1. High-chromium cast iron has poor toughness and is prone to cracking during the production and transportation of parts; 2. The cost of inlaying carbide columns is too high; 3. The wear-resistant life of the surfacing material is low, and the welding wire surfacing requires frequent disassembly and maintenance, resulting in low production efficiency; 4. The density of carbide or other metal materials is high, resulting in high motor output power and high equipment cost; high power consumption during user use, high sand making cost; large bearing stress on the rotating bearing of the equipment and short service life; 5. Due to the high hardness of the wear-resistant material, it is difficult to form and process the parts, and the freedom of part structure design is limited. Summary of the invention
[0004] The present application provides a composite material and a preparation method thereof, a dividing cone and a preparation method thereof, which can increase the service life of the dividing cone.
[0005] The embodiment of the present application is implemented as follows:
[0006] In a first aspect, the present application example provides a method for preparing a composite material, comprising: mixing ceramic particles, a binder and water glass and sintering to obtain a ceramic preform having a porous structure, pouring a first molten iron into a mold, and placing the ceramic preform into the mold for extrusion casting so that the first molten iron enters the pores of the ceramic preform.
[0007] Optionally, the ceramic particles include ZTA, Al2O3, ZrO2, B4C, TiC, VC, ZrC, NbC, WC, SiC, Si3N4, AlN or TiB2.
[0008] Optionally, the first molten iron is obtained by smelting high chromium cast iron, high manganese steel or low alloy steel.
[0009] In the above technical solution, the preparation method of the present application can prepare a porous material in which the first molten iron is filled in the pores of the ceramic preform and solidified. This composite material has good wear resistance and is used to prepare the wear-resistant body of the dividing surface of the dividing cone, so that the service life of the dividing cone is increased by more than 3 times (600h). At the same time, the density of the ceramic preform is relatively low, which is 1.8-3.6g / cm 3 , so that the weight of the material distribution cone with the wear-resistant body made of the composite material is reduced, thereby reducing the motor power output and bearing loss. The preparation method of the present application is simple and the raw materials are low-cost.
[0010] In combination with the first aspect, in a first possible example of the first aspect of the present application, the volume fraction of the first molten iron in the composite material after solidification is 30-60%.
[0011] Optionally, the pressure of the squeeze casting is 100 to 300 MPa, and the holding time is 60 to 180 s.
[0012] Optionally, after the extrusion casting is completed, the mold is cooled to 100-200° C., then heated to 180-350° C. for tempering, and then cooled to room temperature.
[0013] In the above example, the volume fraction of the first molten iron in the composite material after solidification is 30-60%, so that the volume fraction of the ceramic preform in the composite material is 40-70%, and the overall density of the composite material is 5.8-7.2 cm / 3 .
[0014] Annealing can partially or completely relieve stresses in composite materials.
[0015] In combination with the first aspect, in a second possible example of the first aspect of the present application, the mass ratio of the ceramic particles, the adhesive and the water glass is 100:1-7:1-7.
[0016] Optionally, the particle size of the ceramic particles is 1.00 to 4.75 mm, and the mass fraction of the ceramic particles with a particle size of 1.40 to 2.36 mm is 20 to 60%.
[0017] Optionally, the sintering temperature is 700-1000° C., and the sintering time is 10-60 min.
[0018] In the above example, ceramic particles, binder and water glass are mixed and sintered according to the above ratio, which is conducive to preparing a ceramic preform with a porous structure.
[0019] In a second aspect, the present application provides a composite material, which is prepared according to the above-mentioned method for preparing the composite material.
[0020] In the above technical solution, the composite material of the present application has good wear resistance and can be used to prepare the wear-resistant body of the dividing surface of the dividing cone, so that the service life of the dividing cone is increased by more than 3 times (600h). At the same time, the density of the composite material is relatively low, and the wear-resistant body made of this composite material reduces the weight of the dividing cone on which the wear-resistant body is installed, thereby reducing the power output of the motor and the bearing loss.
[0021] In a third aspect, the present application example provides a distributor cone, which includes a base and a wear-resistant body.
[0022] The base is provided with an annular dividing surface, on which a plurality of inlay grooves are arranged surrounding the center of the dividing surface.
[0023] A plurality of wear-resistant bodies are made of the composite material, and the plurality of wear-resistant bodies are embedded in a plurality of embedding grooves.
[0024] In the above technical solution, the dividing cone of the present application is embedded with a plurality of wear-resistant bodies on the dividing surface of the base, thereby improving the wear resistance of the dividing surface, protecting the base, and reducing the amount of wear.
[0025] In combination with the third aspect, in a first possible example of the third aspect of the present application, the wear-resistant body protrudes from the dividing surface.
[0026] Optionally, the wear-resistant body is 3 to 7 mm higher than the dividing surface.
[0027] In the above example, the wear-resistant body protruding from the dividing surface can increase the contact area with the material and reduce the high-speed scraping between the material and the dividing cone during the high-speed rotation of the dividing cone. The groove between any two adjacent wear-resistant bodies can quickly eject the material.
[0028] In combination with the third aspect, in a second possible example of the third aspect of the present application, 5 to 18 inlay grooves are arranged on the above-mentioned dividing surface.
[0029] In a fourth aspect, the present application example provides a method for preparing the above-mentioned dividing cone, which is prepared by a sand casting method, comprising: placing a preheated wear-resistant body into a sand mold, and then pouring a second molten iron into the sand mold.
[0030] Optionally, the second molten iron is obtained by smelting ductile iron, high manganese steel or high chromium cast iron.
[0031] In the above technical solution, the preparation method of the present application uses the second molten iron to cast and bond the wear-resistant body, which can make up for the defects of the impact toughness step of the composite material. The preparation method of the present application is simple and the structure of the obtained dividing cone is stable.
[0032] In combination with the fourth aspect, in a first possible example of the fourth aspect of the present application, the preheating includes preheating the wear-resistant body at 700 to 900° C. for 15 to 60 minutes.
[0033] Optionally, before preheating, the plurality of wear-resistant bodies are fixed to form a target shape.
[0034] In combination with the fourth aspect, in a second possible example of the fourth aspect of the present application, after the second molten iron is poured into the sand mold, the temperature is lowered to 100-200°C and the sand is cleared to make a dividing cone. The dividing cone is then heated to 950-1000°C at a heating rate of 2-5 min / °C, kept warm for 2-4 hours, and then quenched to 300-350°C. The dividing cone is then buried in the sand, cooled to 100-150°C, taken out of the sand, and then heated to 250-300°C at a heating rate of 5-10 min / °C, kept warm for 2-4 hours, and cooled to room temperature.
[0035] In the above example, quenching can ensure the martensitic transformation of the composite material wear-resistant body, thereby improving hardness and wear resistance; tempering can relieve stress and prevent parts from cracking. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 This is a schematic diagram of the structure of a material distribution cone according to an embodiment of the present application;
[0038] Figure 2 A schematic diagram of the structure of a base according to an embodiment of the present application;
[0039] Figure 3 The embodiment of the present application uses a plurality of wear-resistant body parts fixed by a frame.
[0040] Icon: 10-dividing cone; 100-base; 101-dividing surface; 102-through hole; 103-inlay groove; 200-wear-resistant body; 300-groove. DETAILED DESCRIPTION
[0041] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0042] The following specifically describes a composite material and a preparation method thereof, a dividing cone and a preparation method thereof according to an embodiment of the present application:
[0043] The present application provides a method for preparing a composite material, comprising: mixing ceramic particles, a binder and water glass and sintering to obtain a ceramic preform with a porous structure, pouring a first molten iron into a mold, and placing the ceramic preform into the mold for extrusion casting so that the first molten iron enters the pores of the ceramic preform.
[0044] The preparation method of the present application can prepare a porous material in which the first molten iron is filled in the pores of the ceramic preform and solidified, and the particle size of the pores of the ceramic preform is ≤1mm. This composite material has good wear resistance and is used to prepare the wear-resistant body of the dividing surface of the dividing cone, so that the service life of the dividing cone is increased by more than 3 times (600h). At the same time, the density of the ceramic preform is relatively low, which is 1.8 to 3.6 g / cm 3 , so that the weight of the material distribution cone with the wear-resistant body made of the composite material is reduced, thereby reducing the motor power output and bearing loss. The preparation method of the present application is simple and the raw materials are low-cost.
[0045] The preparation method of the composite material of the present application comprises the following steps:
[0046] 1. Preparation of ceramic preform
[0047] The ceramic particles, the binder and the water glass are stirred and mixed to obtain a mixture, and then the mixture is placed in a ceramic preform mold. Finally, the ceramic preform mold containing the mixture is placed in a muffle furnace for sintering.
[0048] The ceramic particles include ZTA (ZrO2 toughened Al2O3), Al2O3, ZrO2, B4C, TiC, VC, ZrC, NbC, WC, SiC, Si3N4, AlN or TiB2. The particle size is 1.00-4.75 mm, and the mass fraction of the ceramic particles with a particle size of 1.40-2.36 mm is 20-60%.
[0049] The adhesive is an inorganic high temperature resistant adhesive, including aluminosilicate material.
[0050] The mass ratio of ceramic particles, adhesive and water glass is 100:1-7:1-7.
[0051] In one embodiment of the present application, the mass ratio of ceramic particles, adhesive and water glass can be 100:6:6. In some other embodiments of the present application, the mass ratio of ceramic particles, adhesive and water glass can also be 100:5:5, or can be 100:7:7, or can be 100:3:4, or can be 100:5:2.
[0052] Optionally, the sintering temperature is 700-1000°C.
[0053] In one embodiment of the present application, the sintering temperature may be 1000° C. In some other embodiments of the present application, the sintering temperature may also be 700° C., 750° C., 800° C., 850° C., 900° C., 950° C. or 980° C.
[0054] Optionally, the sintering time is 10 to 60 minutes.
[0055] In one embodiment of the present application, the sintering time may be 60 min. In some other embodiments of the present application, the sintering time may also be 10 min, 20 min, 30 min, 40 min, 50 min or 55 min.
[0056] 2. Preparation of composite materials
[0057] The first molten iron is poured into the mold, and the ceramic preform obtained by sintering is quickly transferred to the mold for extrusion casting. After the extrusion casting is completed, the temperature is reduced to 100-200°C, and then placed in a muffle furnace and heated to 180-350°C for 2-4 hours, and finally air-cooled to room temperature.
[0058] Optionally, the first molten iron is obtained by smelting high chromium cast iron, high manganese steel or low alloy steel.
[0059] The chromium content of high chromium cast iron is 15-28wt%, and the iron content is more than 60wt%.
[0060] Optionally, the grade of high chromium cast iron selected in the present application is BTMCr15, BTMCr20 or BTMCr26.
[0061] Optionally, the transfer time is within 10 s.
[0062] It should be noted that when the transfer time is within 10 seconds, the temperature of the ceramic preform is still maintained at 700-1000° C., which is conducive to extrusion casting. When the temperature of the ceramic preform drops below 700° C., the ceramic preform needs to be heated before extrusion casting can be performed.
[0063] The pressure of squeeze casting is 100-300MPa.
[0064] In one embodiment of the present application, the pressure of the squeeze casting may be 200 MPa. In some other embodiments of the present application, the pressure of the squeeze casting may also be 100 MPa, 150 MPa, 180 MPa, 220 MPa, 250 MPa or 300 MPa.
[0065] The holding time of squeeze casting is 60 to 180 seconds.
[0066] In one embodiment of the present application, the holding time of squeeze casting can be 60 seconds. In some other embodiments of the present application, the holding time of squeeze casting can also be 70 seconds, 80 seconds, 90 seconds, 100 seconds, 110 seconds, 120 seconds, 130 seconds, 140 seconds, 150 seconds, 160 seconds, 170 seconds or 180 seconds.
[0067] After extrusion molding, the parts are first cooled by the cooling system of the mold to 650-750°C, then air-cooled to 100-150°C after being removed from the mold, and then tempered.
[0068] Tempering can eliminate some or all of the stress within the part and prevent parts made of composite materials from cracking.
[0069] The volume fraction of the first molten iron in the composite material prepared in the present application after solidification is 30-60%, and the volume fraction of the ceramic preform is 40-70%.
[0070] In one embodiment of the present application, the volume fraction of the first molten iron in the composite material after solidification is 50%, and the volume fraction of the ceramic preform is 50%. In some other embodiments of the present application, the volume fraction of the first molten iron in the composite material after solidification can also be 30%, and the volume fraction of the ceramic preform is 70%; or the volume fraction of the first molten iron in the composite material after solidification is 40%, and the volume fraction of the ceramic preform is 60%; or the volume fraction of the first molten iron in the composite material after solidification is 60%, and the volume fraction of the ceramic preform is 40%.
[0071] The natural bulk density of the ceramic preform is 1.8 to 3.6 g / cm 3 , when the content of the ceramic preform in the composite material is higher, the density of the composite material is lower.
[0072] The present application also provides a composite material, which is prepared according to the above-mentioned method for preparing the composite material.
[0073] The composite material of the present application has good wear resistance and can be used to prepare the wear-resistant body of the dividing surface of the dividing cone, so that the service life of the dividing cone is increased by more than 3 times (600 hours). At the same time, the density of the composite material is relatively low, and the wear-resistant body made of the composite material reduces the weight of the dividing cone on which the wear-resistant body is installed, thereby reducing the power output of the motor and the bearing loss.
[0074] See also Figure 1 The present application also provides a dividing cone 10 , the upper portion of the dividing cone 10 is conical, the lower portion of the dividing cone 10 is cylindrical, and the dividing cone 10 includes a base 100 and a wear-resistant body 200 .
[0075] See also Figure 2 The upper surface of the base 100 is a material dividing surface 101, and the base 100 is provided with a through hole 102 in the middle thereof along the axial direction, and the material dividing surface 101 is distributed around the through hole 102. The material dividing surface 101 is a curved surface, and its shape is similar to the side of a cone, but without a cone tip.
[0076] The dividing surface 101 is provided with a plurality of inlay grooves 103 surrounding the through hole 102 .
[0077] In such Figure 2 In the illustrated embodiment, the multiple inlay grooves 103 have the same shape and size, and the multiple inlay grooves 103 are evenly distributed on the dividing surface 101, and along the longitudinal direction of the dividing surface 101, each inlay groove 103 extends from a position close to the through hole 102 to the edge of the dividing surface 101. In some other embodiments of the present application, the shape and size of each inlay groove 103 may be different and formed according to actual needs.
[0078] The number of the mounting grooves 103 is 5 to 18.
[0079] In such Figure 2 In the illustrated embodiment, the dividing surface 101 is provided with 9 evenly arranged inlay grooves 103. In other embodiments of the present application, the dividing surface 101 may also be provided with 5, 6, 7, 8, 10, 11, 12, 13, 14, 15, 16, 17 or 18 inlay grooves 103.
[0080] See also Figure 1 , multiple wear-resistant bodies 200 are embedded in multiple embedding grooves 103.
[0081] It should be noted that the present application does not limit the number of wear-resistant bodies 200 in each embedding groove 103 .
[0082] In such Figure 1In the illustrated embodiment, one wear-resistant body 200 is disposed in each mounting groove 103. In some other embodiments of the present application, two, three or more wear-resistant bodies 200 may also be disposed in each mounting groove 103, but the plurality of wear-resistant bodies 200 need to cooperate with each other to fill each mounting groove 103 so that each wear-resistant body 200 is stably disposed in the mounting groove 103.
[0083] The wear-resistant bodies 200 protrude from the material dividing surface 101 to form a step, and a groove 300 is provided between any two adjacent wear-resistant bodies 200 .
[0084] On the one hand, this protruding structure can protect the base 100 and reduce the wear of the base 100; on the other hand, during the high-speed rotation of the dividing cone 10, it increases the contact area with the material and reduces the high-speed scraping between the material and the dividing cone 10. The groove 300 between any two adjacent wear-resistant bodies 200 can quickly eject the material.
[0085] Optionally, the wear-resistant body 200 is higher than the dividing surface 101 .
[0086] In such Figure 1 In the illustrated embodiment, the wear-resistant body 200 is 5 mm higher than the dividing surface 101. In some other embodiments of the present application, the wear-resistant body 200 may also be 4 mm, 6 mm or 7 mm higher than the dividing surface 101.
[0087] The width of the groove 300 is 10 to 30 mm.
[0088] In such Figure 1 and 2 In the embodiment shown, the width of the groove 300 is 20 mm. In some other embodiments of the present application, the width of the groove 300 may also be 10 mm, 15 mm, 25 mm or 30 mm.
[0089] In order to make the groove 300 linear, the upper surface of the protruding wear-resistant body 200 is trapezoidal, and the two adjacent waistlines of any two adjacent wear-resistant bodies 200 are parallel.
[0090] The present application also provides a method for preparing the above-mentioned dividing cone 10, wherein the dividing cone 10 of the present application is prepared by a sand casting method, wherein the wear-resistant body 200 is made of the above-mentioned composite material, and the base 100 is made of ductile iron, high manganese steel or high chromium cast iron.
[0091] Optionally, the base 100 is made of ductile iron or high manganese steel.
[0092] Ductile iron and high manganese steel have a hardness of 200-300HB, which is easy to machine. They can be processed into various complex shapes or mounting holes and mounting surfaces according to equipment requirements, thereby achieving good assembly requirements with other equipment components. However, high chromium cast iron has a hardness of more than 58HRC, which is difficult to process and has high cost, thus limiting the freedom of part design.
[0093] Optionally, the grade of ductile iron used in the present application is QT400, QT450 or QT500.
[0094] Optionally, the grade of high manganese steel used in this application is Mn13 or Mn18.
[0095] The preparation method of the dividing cone 10 of the present application comprises the following steps:
[0096] 1. Preparation of wear-resistant body 200 parts
[0097] The composite material preparation method is used to form 5 to 18 sector-shaped wear-resistant body 200 parts. In addition, in order to reduce the cost of making the mold, the shapes and sizes of the multiple wear-resistant body 200 parts are consistent and can be formed using the same mold. The prepared wear-resistant body 200 parts can be suitable for the dividing cone 10 of multiple sizes.
[0098] Then the prepared wear-resistant body 200 parts are polished to remove the oxide scale. A plurality of wear-resistant body 200 parts are fixed with a frame to form a cone, such as Figure 3 As shown, put it into a box furnace for preheating treatment.
[0099] The preheating treatment includes preheating the fixed wear-resistant body 200 part at 700 to 900° C. for 15 to 60 minutes.
[0100] 2. Preparation of the second molten iron
[0101] The configured molten raw materials are put into a medium frequency induction furnace for smelting according to the material distribution requirements, and then the second molten iron is spheroidized, inoculated and modified in a ladle after being taken out of the furnace.
[0102] The melting temperature is 1450~1700℃.
[0103] When the molten raw material is ductile cast iron, the smelting temperature is 1450-1520°C;
[0104] When the molten raw material is high manganese steel, the smelting temperature is 1480~1600℃;
[0105] When the molten raw material is high chromium cast iron, the smelting temperature is 1500-1700℃.
[0106] 3. Preparation of dividing cone 10
[0107] The sand is piled up in the box to form a sand mold, and the bottom of the sand mold is built into the shape of the fixed wear-resistant body 200 part. The preheated and fixed wear-resistant body 200 part is placed at the bottom of the sand mold, and then the treated second molten iron is poured into the sand mold. After air cooling to 100-200°C, the box is opened and the sand is cleaned to obtain a dividing cone 10.
[0108] The obtained dividing cone 10 is heat-treated, and the heat treatment includes heating the dividing cone 10 to 950-1000°C at a heating rate of 2-5 min / °C, keeping it warm for 2-4 hours, then quenching it to 300-350°C, burying the dividing cone 10 in sand, cooling it to 100-150°C, taking the dividing cone 10 out of the sand, and then putting it into a low-temperature furnace that has been preheated to 100-150°C, heating it to 250-300°C at a heating rate of 5-10 min / °C, keeping it warm for 2-4 hours, and cooling it to room temperature.
[0109] The composite material and its preparation method, the dividing cone and its preparation method of the present application are further described in detail below in conjunction with the embodiments.
[0110] Example 1
[0111] The present invention provides a composite material and a method for preparing the composite material, which comprises the following steps:
[0112] 1. Preparation of ceramic preform
[0113] 100 parts by weight of ZTA ceramic particles, 4 parts by weight of inorganic high temperature resistant glue and 4 parts by weight of water glass were stirred and mixed to prepare a mixture, and then the mixture was placed in a ceramic preform mold. Finally, the ceramic preform mold containing the mixture was placed in a muffle furnace and sintered at 1000° C. for 1 hour.
[0114] 2. Preparation of composite materials
[0115] Molten iron of brand BTMCr15 is poured into the mold, and the ceramic preform obtained by sintering is transferred to the mold for extrusion casting within 10 seconds. The pressure of extrusion casting is 250MPa, and the pressure is maintained for 60 seconds. After extrusion casting, the temperature is cooled to 150℃, and then placed in a muffle furnace and heated to 260℃ for 3 hours, and finally air-cooled to room temperature.
[0116] In the composite material prepared in the embodiment of the present application, the volume fraction of high chromium cast iron is 50%, and the volume fraction of the ceramic preform is 50%.
[0117] Example 2
[0118] The present invention provides a composite material and a method for preparing the composite material, which comprises the following steps:
[0119] 1. Preparation of ceramic preform
[0120] 100 parts by weight of ZTA ceramic particles, 5 parts by weight of inorganic high temperature resistant glue and 5 parts by weight of water glass were stirred and mixed to prepare a mixture, and then the mixture was put into a ceramic preform mold. Finally, the ceramic preform mold containing the mixture was put into a muffle furnace and sintered at 700° C. for 10 minutes.
[0121] 2. Preparation of composite materials
[0122] Molten iron of brand BTMCr20 is poured into the mold, and the ceramic preform obtained by sintering is transferred to the mold for extrusion casting within 10 seconds. The pressure of extrusion casting is 150MPa, and the pressure is maintained for 90 seconds. After extrusion casting is completed, the temperature is cooled to 100℃, and then placed in a muffle furnace and heated to 180℃ for 4 hours, and finally air-cooled to room temperature.
[0123] In the composite material prepared in the embodiment of the present application, the volume fraction of high chromium cast iron is 30%, and the volume fraction of the ceramic preform is 70%.
[0124] Example 3
[0125] The present invention provides a composite material and a method for preparing the composite material, which comprises the following steps:
[0126] 1. Preparation of ceramic preform
[0127] 100 parts by weight of ZTA ceramic particles, 6 parts by weight of inorganic high temperature resistant glue and 6 parts by weight of water glass were stirred and mixed to prepare a mixture, and then the mixture was put into a ceramic preform mold, and finally the ceramic preform mold containing the mixture was put into a muffle furnace and sintered at 800° C. for 30 minutes.
[0128] 2. Preparation of composite materials
[0129] Molten iron of grade Gr26 is poured into the mold, and the ceramic preform obtained by sintering is transferred to the mold for extrusion casting within 10 seconds. The pressure of extrusion casting is 200MPa, and the pressure is maintained for 120 seconds. After extrusion casting, the temperature is cooled to 150℃, and then placed in a muffle furnace and heated to 350℃ for 2 hours, and finally air-cooled to room temperature.
[0130] In the composite material prepared in the embodiment of the present application, the volume fraction of high chromium cast iron is 60%, and the volume fraction of the ceramic preform is 40%.
[0131] Example 4
[0132] The present application provides a dividing cone 10 and a preparation method thereof, which comprises the following steps:
[0133] 1. Preparation of wear-resistant body 200 parts
[0134] The preparation method of the composite material of Example 1 was used to form 9 sector-shaped wear-resistant body 200 parts. Moreover, the shapes and sizes of the multiple wear-resistant body 200 parts were consistent. Then, the prepared wear-resistant body 200 parts were polished to remove the oxide scale. The multiple wear-resistant body 200 parts were fixed with a frame to form a cone, and placed in a box furnace for preheating at 800° C. for 30 minutes.
[0135] 2. Preparation of molten iron
[0136] Ductile iron with the brand QT400 is put into a medium frequency induction furnace for smelting according to the material distribution requirements, and then the molten iron is spheroidized, inoculated and modified in the ladle after it is taken out of the furnace.
[0137] 3. Preparation of dividing cone 10
[0138] The sand is piled up in the box to form a sand mold, and the bottom of the sand mold is built into the shape of the fixed wear-resistant body 200 part. The preheated and fixed wear-resistant body 200 part is placed at the bottom of the sand mold, and then the treated molten iron is poured into the sand mold. After air cooling to 150°C, the box is opened and the sand is cleaned to obtain a dividing cone 10.
[0139] The prepared dividing cone 10 is heat-treated, and the heat treatment includes heating the dividing cone 10 to 980°C at a heating rate of 2 min / °C, keeping it warm for 2 hours, and then quenching it to 350°C, burying the dividing cone 10 in sand, cooling it to 150°C, taking the dividing cone 10 out of the sand, and then putting it into a low-temperature furnace that has been preheated to 150°C, heating it to 260°C at a heating rate of 5 min / °C, keeping it warm for 4 hours, and cooling it to room temperature.
[0140] Example 5
[0141] The present application provides a dividing cone 10 and a preparation method thereof, which comprises the following steps:
[0142] 1. Preparation of wear-resistant body 200 parts
[0143] The preparation method of the composite material of Example 1 was used to form 9 sector-shaped wear-resistant body 200 parts. Moreover, the shapes and sizes of the multiple wear-resistant body 200 parts were consistent. Then, the prepared wear-resistant body 200 parts were polished to remove the oxide scale. The multiple wear-resistant body 200 parts were fixed with a frame to form a cone, and placed in a box furnace for preheating at 700° C. for 60 minutes.
[0144] 2. Preparation of molten iron
[0145] The ductile iron of grade QT450 is put into a medium frequency induction furnace for smelting according to the material distribution requirements, and then the molten iron is spheroidized, inoculated and modified in the ladle after being taken out of the furnace.
[0146] 3. Preparation of dividing cone 10
[0147] The sand is piled up in the box to form a sand mold, and the bottom of the sand mold is built into the shape of the fixed wear-resistant body 200 part. The preheated and fixed wear-resistant body 200 part is placed at the bottom of the sand mold, and then the treated molten iron is poured into the sand mold. After air cooling to 100°C, the box is opened and the sand is cleaned to obtain a dividing cone 10.
[0148] The prepared dividing cone 10 is heat treated, which includes heating the dividing cone 10 to 950°C at a heating rate of 3 min / °C, keeping it warm for 4 hours, then quenching it to 300°C, burying the dividing cone 10 in sand, cooling it to 10°C, taking the dividing cone 10 out of the sand, and then putting it into a low-temperature furnace that has been preheated to 100°C, heating it to 250°C at a heating rate of 6 min / °C, keeping it warm for 2 hours, and cooling it to room temperature.
[0149] Example 6
[0150] The present application provides a dividing cone 10 and a preparation method thereof, which comprises the following steps:
[0151] 1. Preparation of wear-resistant body 200 parts
[0152] The preparation method of the composite material of Example 1 was used to form 9 sector-shaped wear-resistant body 200 parts. Moreover, the shapes and sizes of the multiple wear-resistant body 200 parts were consistent. Then, the prepared wear-resistant body 200 parts were polished to remove the oxide scale. The multiple wear-resistant body 200 parts were fixed with a frame to form a cone, and placed in a box furnace for preheating at 900° C. for 15 minutes.
[0153] 2. Preparation of molten iron
[0154] The high manganese steel with grade Mn13 is put into the medium frequency induction furnace for smelting according to the material requirements, and then the molten iron is spheroidized, inoculated and modified in the ladle after being taken out of the furnace.
[0155] 3. Preparation of dividing cone 10
[0156] The sand is piled up in the box to form a sand mold, and the bottom of the sand mold is built into the shape of the fixed wear-resistant body 200 part. The preheated and fixed wear-resistant body 200 part is placed at the bottom of the sand mold, and then the treated molten iron is poured into the sand mold. After air cooling to 200°C, the box is opened and the sand is cleaned to obtain a dividing cone 10.
[0157] The prepared dividing cone 10 is heat-treated, and the heat treatment includes heating the dividing cone 10 to 1000°C at a heating rate of 5 min / °C, keeping it warm for 3 hours, and then quenching it to 320°C, burying the dividing cone 10 in sand, cooling it to 150°C, taking the dividing cone 10 out of the sand, and then putting it into a low-temperature furnace that has been preheated to 150°C, heating it to 300°C at a heating rate of 10 min / °C, keeping it warm for 2 hours, and cooling it to room temperature.
[0158] Comparative Example 1
[0159] According to the shape of the dividing cone part, the corresponding sand mold is prepared, and high chromium cast iron molten iron (BTMCr26 material is selected) is directly poured, and then the sand is removed and quenched and tempered to obtain a high chromium cast iron dividing cone.
[0160] Test Example 1
[0161] The composite materials prepared in Examples 1 to 3 were respectively taken, and their densities were measured by the Archimedes drainage method, and their hardness was measured by a Rockwell hardness tester. The results are shown in Table 1.
[0162] Table 1 Parameters of the composite materials of Examples 1 to 3
[0163] project Example 1 Example 2 Example 3 <![CDATA[Density g / cm 3 > 6.4 5.9 6.7 Ceramic hardness HV 1400~1600 1400~1600 1400~1600 High chromium cast iron metal matrix hardness HRC 58~60 58~60 58~60
[0164] Test Example 2
[0165] The dividing cones of Example 5 and Comparative Example 1 were respectively taken and installed in a vertical shaft crusher, and their service lives were tested under hard granite conditions, as shown in Table 2.
[0166] Table 2 Service life of the dividing cone of Example 5 and Comparative Example 1
[0167] project Example 5 Comparative Example 1 Service life (h) 501 150
[0168] In summary, the composite material provided in the embodiment of the present application has good toughness, high parts qualification rate, and parts that are not easy to crack during transportation. The elongation after fracture of ductile iron or high manganese steel is above 10%, and the impact toughness is high. Using this metal material to cast and bond the wear-resistant body 200 to form a scoring cone 10 can well make up for the defect of insufficient impact toughness of the composite material or high chromium cast iron.
[0169] At the same time, the wear-resistant body 200 made of composite materials has a simple structure and low mold cost, and can be quickly, simply, and mass-produced. The prefabricated ceramic volume accounts for 40-70% of the composite material, and the rest is high-chromium cast iron, with less ceramic usage and low raw material cost. When making the base 100, lower-cost ductile iron or high-manganese steel is used for bonding. Since the wear-resistant body 200 is a basic structural unit, the advantages of structural optimization can be fully utilized, and it can be spliced according to actual working conditions, and the wear-resistant body 200 can be placed where wear resistance is most needed. It has great cost advantages compared to cemented carbide columns.
[0170] In addition, the service life of ordinary high-chromium cast iron under hard granite conditions is generally 200 hours, after which it needs to be shut down for disassembly and replacement. The use of the composite material to make the dividing cone 10 has a wear life of more than three times that of the original high-chromium cast iron material because the thickness of the wear-resistant body 200 is deep and adjustable. Compared with the original surfacing material, the wear-resistant layer thickness is limited due to the surfacing process, and the surfacing is easy to crack and fall off from the base 100, so the wear life is limited compared to the original high-chromium cast iron. Moreover, disassembling parts from the running equipment for surfacing takes up production time, which seriously affects production efficiency.
[0171] Since 200% of the wear-resistant body is a ceramic preform, the density of the ceramic preform is only 1.8-3.6 g / cm 3 Moreover, the middle part of the dividing cone 10 is the wear-resistant body 200, and the ductile cast iron accounts for a small proportion, which only plays the role of bonding and supporting the wear-resistant body 200. Therefore, the weight of the dividing cone 10 parts can be reduced by more than 10% compared with the original high-chromium cast iron. It has a good effect of lightweighting the components and can reduce the motor power output and bearing loss.
[0172] The above description is only a specific embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A material distribution cone, characterized in that: The upper part of the material distribution cone is conical, the lower part of the material distribution cone is cylindrical, and the material distribution cone includes: A base, wherein the upper surface of the base has a dividing surface, the base is provided with a through hole in the middle along the axial direction, the dividing surface is distributed around the through hole, the dividing surface is a curved surface, and the dividing surface is provided with a plurality of inlay grooves arranged around the center of the dividing surface; A plurality of wear-resistant bodies made of composite materials, wherein the plurality of wear-resistant bodies are embedded in the plurality of embedding grooves, the wear-resistant bodies protrude from the material dividing surface to form steps, and a groove is provided between any two adjacent wear-resistant bodies; The composite material is prepared by the following method: Ceramic particles, a binder and water glass are mixed and sintered to obtain a ceramic preform with a porous structure, wherein the sintering temperature is 700-1000° C. and the sintering time is 10-60 min, first molten iron is poured into a mold, and the ceramic preform is placed in the mold for extrusion casting so that the first molten iron enters the pores of the ceramic preform, and after the extrusion casting is completed, the preform is cooled to 100-200° C. after being ejected from the mold, heated to 180-350° C. for tempering, and cooled to room temperature to obtain a composite material; The ceramic particles include ZTA, Al2O3, ZrO2, B4C, TiC, VC, ZrC, NbC, WC, SiC, Si3N4, AlN or TiB2; The first molten iron is obtained by smelting high chromium cast iron, high manganese steel or low alloy steel.
2. The dividing cone according to claim 1, characterized in that: The wear-resistant body is 3-7 mm higher than the dividing surface.
3. The dividing cone according to claim 1, characterized in that: The dividing surface is provided with 5 to 18 inlay grooves.
4. The dividing cone according to claim 1, characterized in that: The volume fraction of the first molten iron in the composite material after solidification is 30-60%.
5. The dividing cone according to claim 2, characterized in that: The pressure of the squeeze casting is 100-300 MPa, and the holding time is 60-180 s.
6. The dividing cone according to claim 1, characterized in that: The mass ratio of the ceramic particles, the adhesive and the water glass is 100:1-7:1-7.
7. The dividing cone according to claim 6, characterized in that: The particle size of the ceramic particles is 1.00-4.75 mm, and the mass fraction of the ceramic particles with a particle size of 1.40-2.36 mm is 20-60%.
8. A method for preparing a dividing cone according to any one of claims 1 to 7, characterized in that: The dividing cone is prepared by a sand casting method, and the preparation method of the dividing cone comprises: placing the preheated wear-resistant body into a sand mold, and then pouring the second molten iron into the sand mold; The second molten iron is obtained by smelting ductile cast iron, high manganese steel or high chromium cast iron.
9. The method for preparing a dividing cone according to claim 8, characterized in that: The preheating includes preheating the wear-resistant body at 700-900° C. for 15-60 minutes.
10. The method for preparing a dividing cone according to claim 9, characterized in that: Before preheating, the plurality of wear-resistant bodies are fixed to form a target shape.
11. The method for preparing a dividing cone according to claim 8, characterized in that: After the second molten iron is poured into the sand mold, the temperature is lowered to 100-200°C, the box is opened and the sand is cleaned to obtain the dividing cone, and then the dividing cone is heated to 950-1000°C at a heating rate of 2-5 min / °C, kept warm for 2-4 hours, and then quenched to 300-350°C, the dividing cone is buried in the sand, the temperature is lowered to 100-150°C, the dividing cone is taken out of the sand, and then the temperature is raised to 250-300°C at a heating rate of 5-10 min / °C, kept warm for 2-4 hours, and cooled to room temperature.
Citation Information
Patent Citations
Crusher rotor body and crusher
CN106238181A
Preparation method of wear-resistant composite material and preparation method of wear-resistant composite material casting
CN111088444A
Preparation method of ceramic metal composite wear-resistant material
CN111318674A
Mineral aggregate distribution disc for cone crusher
CN211989114U
Material distributing cone
CN214416618U